The Prognostic Value of Indoleamine-2,3-Dioxygenase Gene Expression in Urine of Prostate Cancer Patients Undergoing Radical Prostatectomy as First Treatment of Choice - Thüring, Michael; Knuchel, Robin; Picchetta, Ludovica; Keller, Daniel; Schmidli, Tobias S.; Provenzano, Maurizio (Frontiers in Immunology, 2020)
Prostate cancer (PCa) is a slow-growing tumor representing one of the major causes of all new cancer cases and cancer mortality in men worldwide. Although screening methods for PCa have substantially improved, the outcome for patients with advanced PCa remains poor. The elucidation of the molecular mechanism that drives the progression from a slow-growing, organ-confined tumor to a highly invasive and castration-resistant PCa (CRPC) is therefore important. We have already proved the diagnostic potential of indoleamine-2,3-dioxygenase (IDO) when detected in urine of individuals at risk of developing PCa. The aim of this study was to implement IDO as a prognostic marker for PCa patients undergoing surgical treatment. We have thus conducted an observational study by collecting 100 urine samples from patients undergoing radical prostatectomy as first treatment of choice. To test the integrity of our investigation, scale dilution cells of an established PC3 cell line were added to urine of healthy donors and used for gene expression analysis by a TaqMan assay on the catalytic part of IDO mRNA. Our data show that the quantification of IDO mRNA in urine of patients has a very promising ability to identify patients at high risk of cancer advancement, as defined by Gleason score. Our goal is to lay the groundwork to develop a superior test for PCa. The data generated are thus necessary (i) to strengthen the IDO-based diagnostic/prognostic test and (ii) to provide patients and clinicians with an affordable and easy screening test.